Sterically Congested Chiral 7, 8‐Dioxa[6]helicene and Its Dihydro Analogues: Synthesis, Regioselective Functionalization, and Unexpected Domino Prins Reaction. Issue 17 (6th May 2015) - Hasan, Mohammed; Pandey, Anita D.; Khose, Vaibhav N.; Mirgane, Nitin A.; Karnik, Anil V.
Abstract: A C 2 ‐symmetric 7, 8‐dioxa[6]helicene‐2, 13‐diol was synthesized from readily available 2, 7‐dihydroxynaphthalene on a gram scale. A high‐yielding synthetic strategy for the regioselective hydroxymethylation at the sterically most hindered C1 position of diol analogues was investigated. The dioxa[6]helicene backbone with configurationally stable helical enantiomers was synthesized, and these enantiomers were separated by HPLC on a chiral stationary phase. We also observed an unexpected domino Prins reaction. This is the first report of a domino Prins reaction occurring on a helicene. Along with the high‐yielding regioselective functionalization of dioxa[6]helicene analogues, the synthesis of a few cis ‐7a, 14c‐dihydro‐functionalized helicenoid diols substituted at the sterically most hindered C1 and C14 positions in their racemic forms was explored. Abstract : Helical dioxa[6]helicene‐based systems are developed by regioselective functionalization at the sterically most hindered C1 position. An unexpected domino Prins reaction on the central double bond of the helicene skeleton is observed as a result of the strain present in the helicene backbone. The steric factors responsible for the reaction outcome are discussed.